A Path Analysis of the Effects of Self-Confidence and Habits of Mind on Students’ Learning Activeness and Mathematical Communication Skills - Halistin Halistin; Mirnawati; Hasrin Lamote; Tandri Patih; Sri Anandari Safaria (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2026)
Learning activeness and mathematical communication skills are core competencies that students must develop in mathematics learning. The development of these competencies is related to and influenced by students' internal factors, namely self-confidence and habits of mind. Sixty-five eleventh-grade students at SMAN 1 Sampara from two classes were selected using a cluster random sampling technique based on the Slovin formula. The instruments used were a questionnaire to measure self-confidence, habits of mind, and learning activity, and a test to measure mathematical communication skills. Data analysis was conducted using path analysis techniques to determine the direct and indirect effects between variables. The results showed that self-confidence (60%), habits of mind (67.69%), learning activity (64.62%), and mathematical communication skills (63.08%) were in the moderate category. Self-confidence and habits of mind have been shown to have a positive and significant influence on students' learning activities. However, no direct or indirect influence of self-confidence, habits of mind, and learning activity on students' mathematical communication skills was found. In conclusion, although self-confidence and thinking habits can increase students' active participation in the learning process, they are not enough to improve their ability to communicate mathematical ideas effectively